The cultural change narrative as a core component of therapeutic change - Tobiassen, Astrid Hermann; Sundal, Thea; Stänicke, Erik; Folmo, Espen Jan (Frontiers in Psychiatry, 2023)
Research indicates a similar effect of Mentalization-based treatment (MBT) and Dialectical behavior therapy (DBT) for borderline personality disorder (BPD). However, there is a paucity in studies investigating the change narrative received from and developed in these treatments. The aim of the present study is to investigate similarities and differences in the change narratives provided by MBT and DBT, and how these narratives reflect the rationale, explanations, and procedures of the provided treatment. The study is a qualitative analysis of seven interviews conducted by the authors. Three of the participants had received MBT, and four of the participants had received DBT. This study presents an interpretative phenomenological analysis (IPA) of the change narratives received in two specialized treatments for BPD. The main findings from the IPA were that the change narratives described by the participants reflected the treatment they received. The DBT participants highlighted explicit learning of tools and techniques, with predictable and safe therapists. In contrast, the MBT participants emphasized a long-lasting process of exploring to create procedural learning with therapists who followed their lead. The participants’ stories of change shed light on how a change narrative was developed, and therefore how the rationale, explanations and procedures were conveyed differently by MBT and DBT.